The eruption of Mount St. Helens, 1980 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Inc., 2016)
On May 18, 1980, eleven-year-old Jessie Marlowe and her best friends, Eddie and Sam, are in a forest near Mount St. Helens when the months of wondering whether the volcano will erupt are finally answered--all three are badly burned, but it is up to Jessie to protect the boys as best she can and hope that somebody comes to rescue them.
3.5
3-6
640
Keywords: Survival -- Fiction; Volcanoes -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Survival skills -- Fiction; Volcanoes -- Fiction; Friendship -- Fiction; Survival -- Fiction; Volcanoes -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Saint Helens, Mount (Wash.) -- Eruption, 1980 -- Fiction; Saint Helens, Mount (Wash.) -- Eruption, 1980 -- Fiction